Reliability and failure modes of narrow implant systems - Hirata, Ronaldo; Bonfante, Estevam A.; Anchieta, Rodolfo B. [UNESP]; Machado, Lucas S. [UNESP]; Freitas, Gileade; Fardin, Vinicius P.; Tovar, Nick; Coelho, Paulo G. (Springer, 2016)
Narrow implants are indicated in areas of limited bone width or when grafting is nonviable. However, the reduction of implant diameter may compromise their performance. This study evaluated the reliability of several narrow implant systems under fatigue, after restored with single-unit crowns. Narrow implant systems were divided (n = 18 each), as follows: Astra (ASC); BioHorizons (BSC); Straumann Roxolid (SNC), Intra-Lock (IMC), and Intra-Lock one-piece abutment (ILO). Maxillary central incisor crowns were cemented and subjected to step-stress accelerated life testing in water. Use level probability Weibull curves and reliability for a mission of 100,000 cycles at 130- and 180-N loads (90 % two-sided confidence intervals) were calculated. Scanning electron microscopy was used for fractography. Reliability for 100,000 cycles at 130 N was similar to 99 % in group ASC, similar to 99 % in BSC, similar to 96 % in SNC, similar to 99 % in IMC, and similar to 100 % in ILO. At 180 N, reliability of similar to 34 % resulted for the ASC group, similar to 91 % for BSC, similar to 53 % for SNC, similar to 70 % for IMC, and similar to 99 % for ILO. Abutment screw fracture was the main failure mode for all groups. Reliability was not different between systems for 100,000 cycles at the 130-N load. A significant decrease was observed at the 180-N load for ASC, SNC, and IMC, whereas it was maintained for BSC and ILO. The investigated narrow implants presented mechanical performance under fatigue that suggests their safe use as single crowns in the anterior region.
Keywords: Dental implants; Biomechanics; Reliability; Weibull; Fatigue